2020
DOI: 10.1016/j.adolescence.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Preference and popularity as distinct forms of status: A meta‐analytic review of 20 years of research

Abstract: Introduction: A systematic meta-analysis was conducted of the association between preference and popularity across childhood and adolescence. The role of development, sex, and region of the world were examined. Method: The analysis was conducted on 135 samples including 136,014 participants. The samples were divided by age (upper grades primary school, k = 41; lower grades secondary school, k = 72; upper grades secondary school, k = 22) and region (North America, k = 54; Europe, k = 66; China, k = 10).Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 215 publications
3
74
1
1
Order By: Relevance
“…Popularity norms may also matter more in secondary school, due to social and pubertal changes that make adolescents more sensitive to peer influence and motivated to change their reputation in the peer group (Steinberg, 2007 ; Veenstra & Laninga-Wijnen, 2021 ). Moreover, there is evidence that children differentiate less between popularity and social preference than adolescents (Van den Berg et al, 2020 ). This could complicate detecting effects of aggressive popularity norms specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popularity norms may also matter more in secondary school, due to social and pubertal changes that make adolescents more sensitive to peer influence and motivated to change their reputation in the peer group (Steinberg, 2007 ; Veenstra & Laninga-Wijnen, 2021 ). Moreover, there is evidence that children differentiate less between popularity and social preference than adolescents (Van den Berg et al, 2020 ). This could complicate detecting effects of aggressive popularity norms specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Popularity was assessed by asking “Who is most popular?” and “Who is least popular?”. A composite score for popularity was computed by subtracting the least popular proportion score from the most popular proportion score (Cillessen & Marks, 2011 ; Van den Berg et al, 2020 ). This score could vary from −1 (nominated by all voters as least popular and by none as most popular) to 1 (nominated by all voters as most popular and by none as least popular).…”
Section: Methodsmentioning
confidence: 99%
“…Peer status plays a pivotal role in adolescent development. Research on peer relations has identified two distinct forms of peer status in the offline context: likeability and peer-perceived popularity (Cillessen & Rose, 2005;van den Berg et al, 2020). Likeability, or social preference, is defined by peer acceptance, higher levels of prosocial behavior, and character traits such as agreeableness, while popularity reflects one's social reputation or high position in a social hierarchy and depends on visibility, power, and influence.…”
Section: Peer Statusmentioning
confidence: 99%
“…Status can be derived from personal preference of an individual student of its peers, indicated by liking a peer or seeing him as a friend, also called social preference. On the other hand, there is a more reputation based status, that refers to which students are perceived by their peers as being most popular, influential and powerful [ 14 ]. Popularity and social preference can thus be seen as two dimensions of social status.…”
Section: Introductionmentioning
confidence: 99%